Proceedings of the 2nd World Congress on Integrated Computational Materials Engineering (ICME) - Li, Mei; Campbell, Carelyn; Thornton, Katsuyo; Holm, Elizabeth; Gumbsch, Peter (Springer International Publishing : Imprint: Springer, 2016)
This book represents a collection of papers presented at the 2nd World Congress on Integrated Computational Materials Engineering (ICME), a specialty conference organized by The Minerals, Metals & Materials Society (TMS).